Factor Influencing Family Support On Prevention of Transmission of Tuberculosis in the work area of the Surabaya city health center - Lembunai Tat Alberta; Dwi Utari Widyastuti (Health Notions, 2021)
Family support and factors affecting it are expected to minimize pulmonary tuberculosis transmission. The study aimed was to analyze the factors that influence family support for the prevention of transmission of pulmonary tuberculosis. This study was a cross-sectional study, with a sample size of 110 pulmonary tuberculosis patients who were treated at the public health center in Surabaya. The instrument used for data collection was a questionnaire. The data analysis used was descriptive analysis and Partial Least Square (PLS). The family support everything is good (71%-86.4%). Most and  almost of the factors receiving support and  supporting factors were in the good category (67.3% and 93.6%).  Composition and structure of social networks support from neighbors and friends (95.5%),  they have a very close relationship  (64.5%). There was a relationship between the factors of recipient support, support providers, composition and structure of social networks on family support in the prevention of pulmonary tuberculosis transmission with p -values of 0.002, 0.000, and 0.000, respectively. Factors of recipient support, support providers, composition and structure of social networks affect family support in the prevention of pulmonary tuberculosis transmission. Nurses must support families in providing support for the prevention of pulmonary tuberculosis transmission .